2012
DOI: 10.1029/2011rs004946
|View full text |Cite
|
Sign up to set email alerts
|

Sharpening our thinking about polar cap ionospheric patch morphology, research, and mitigation techniques

Abstract: Since polar cap patches were discovered, their nature, physics, and impact on navigation and communication signals has been repeatedly addressed. Both terminology and inference of physical processes from diverse instruments have introduced confusion. Poleward moving auroral form is a morphological descriptor but cannot be equated to an island of high‐density plasma. Particle precipitation produces low‐density patches, but high‐density patches derive from solar produced plasma. The challenge of patches is findi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
190
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(196 citation statements)
references
References 73 publications
6
190
0
Order By: Relevance
“…However, the seasonal dependence of polar patches is still an open issue: some studies reported that the polar patches are mainly a local winter phenomenon in both hemispheres (e.g., Coley and Heelis, 1998;Kivanç and Heelis, 1998;Carlson, 2012;Spicher et al, 2017), while there are also studies found that polar patches have higher occurrence during December solstice months in both hemispheres (e.g., Noja et al, 2013;Chartier et al, 2018). Our result shown in Fig.…”
Section: Seasonal Dependence Of Gps Signal Losssupporting
confidence: 69%
See 1 more Smart Citation
“…However, the seasonal dependence of polar patches is still an open issue: some studies reported that the polar patches are mainly a local winter phenomenon in both hemispheres (e.g., Coley and Heelis, 1998;Kivanç and Heelis, 1998;Carlson, 2012;Spicher et al, 2017), while there are also studies found that polar patches have higher occurrence during December solstice months in both hemispheres (e.g., Noja et al, 2013;Chartier et al, 2018). Our result shown in Fig.…”
Section: Seasonal Dependence Of Gps Signal Losssupporting
confidence: 69%
“…The density gradient generally show larger values at 70-80 • |MLAT| on the dayside (09:00-15:00 MLT) and at 60-70 • |MLAT| on the nightside. This kind of distribution, with largest plasma density gradients in the cusp region at noon and with a "tail" reaching from afternoon to midnight at lower latitudes at 60-70 • |MLAT|, is considered to be caused by the tongue of ionization (TOI) phenomenon, which is attributed to be a major source of polar patches (e.g., Hosokawa et al, 2010;Carlson, 2012). Figures 4d and e present the electron density gradient distribution derived only from the orbits without GPS signal loss events detected.…”
Section: Gps Signal Loss Event Detectionmentioning
confidence: 99%
“…Within the auroral zone there is a lot of free energy to drive various instabilities. Obviously, there may be velocity shears associated with auroral arcs that can rapidly develop small scale irregularities on large scale structures (auroral blobs) by the KelvinHelmholtz type, velocity shear Instability (KHI) (Kersley et al 1988;Keskinen et al 1988;Carlson et al 2008;Carlson 2012). The auroral precipitation interacting with the polar cap patches may give rise to plasma gradients on which the GDI can operate as has been documented in the dayside cusp (Moen et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Both Carlson (2012) and Zhang et al (2013) have provided analyses of events using, respectively, EISCAT for Ne data and GPS receiver arrays for TEC. The latter dataset is overlaid with SuperDARN convection patterns.…”
Section: Search For Observational Supportmentioning
confidence: 99%
“…For ease of reference we use the word "patch" in this paper, but with that term we don't mean only features that are two times or greater in density than the background, which is its conventional definition (e.g. Carlson, 2012).…”
mentioning
confidence: 99%